Matematică
cristinab
3

Descumpuneti, aplicati formulele, factorul comun si artifici: 5x³-45x= 7x³-28x= x5-16x= x³+x²+x+1= x³+3x²-x-3= x³-2x³-x+2= x³-4x²-4x+16= x³+3x²-4x-12= x³+3x²-9x-27= x³+2x²-16(x+2)= 9(2x-5)²-4(4x-3)²= 4x²-9-(2x+3)²= 9(x-2)²-4(3x-7)²= 4(5x+3)²-25(x-2)²= (2x²-2x+5)²-(x²+2x+2)²= x²+3x+2= x²+5x+4= x²+7x+12= x²+8x+15= x²+9x+14= x2+11x=30= x²+15x+56= x2+12x+35= x²-5x+6= x²-9x+20=

+0
(2) Răspunsuri
ginutza

1) 5x(x la puterea 2-9)  2) 7x(x la puterea 2-4)  3) x(5-16)  4) x la puterea 3(x+1) la puterea 2 de la 5-15 nu stiu sa fac  16) (x+1)(x+2)  17) (x+1)(x+4)  18) (x+3)(x+4)  19) (x+5)(x+3)  20) (x+2)(x+7)  21) -  22)   23) (x+5)(x+7)  24) (x-5)(x+1)  25) -

laru

5x³-45x= 7x³-28x=7x(x²-4)=7x(x-2)(x+2) x⁵-16x=x(x⁴-16)=x(x²-4)(x²+4)=x(x+2)(x-2)(x²+4) x³+x²+x+1=x²(x+1)+(x+1)=(x+1)(x²+1) x³+3x²-x-3=x²(x+3)-(x+3)=(x+3)(x²-1)=(x+3)(x-1)(x+1) x³-2x²-x+2=x²(x-2)-(x-2)=(x-2)(x²-1)=(x-2)(x-1)(x+1) x³-4x²-4x+16=x²(x-4)-4(x-4)=(x-4)(x²-4)=(x-4)(x-2)(x+2) x³+3x²-4x-12=x²(x+3)-4(x+3)=(x+3)(x²-4)=(x+3)(x-2)(x+2) x³+3x²-9x-27=x²(x+3)-9(x+3)=(x+3)(x²-9)=(x+3)(x-3)(x+3) x³+2x²-16(x+2)=x²(x+2)-16(x+2)=(x+2)(x²-16)=(x+2)(x-4)(x+4) 9(2x-5)²-4(4x-3)²=[3(2x-5)-2(4x-3)][3(2x-5)+2(4x-3)]= =(6x-15-8x+6)(6x-15+8x-6)=(-2x-9)(14x-21)=7(-2x-9)(2x-3) 4x²-9-(2x+3)²=(2x-3)(2x+3)-(2x+3)²=(2x+3)(2x-3-2x-3)=-6(2x+3) 9(x-2)²-4(3x-7)²=[3(x-2)-2(3x-7)][3(x-2)+2(3x-7)]= =(3x-6-6x+14)(3x-6+6x-14)=(-3x+8)(9x-20) 4(5x+3)²-25(x-2)²=[2(5x+3)-5(x-2)][2(5x+3)+5(x-2)]= =(10x+6-5x+10)(10x+6+5x-10)=(5x+16)(15x-4) (2x²-2x+5)²-(x²+2x+2)²=(2x²-2x+5-x²-2x-2)(2x²-2x+5+x²+2x+2)= =(2x²-2x+5-x²-2x-2)(2x²-2x+5+x²+2x+2)=(x²-4x+3)(3x²+7)=(x²-x-3x+3)(3x²+7)= =[x(x-1)-3(x-1)](3x²+7)=(x-1)(x-3)(3x²+7) x²+3x+2=x²+2x+x+2=x(x+2)+(x+2)=(x+2)(x+1) x²+5x+4=x²+4x+x+4=x(x+4)+(x+4)=(x+4)(x+1) x²+7x+12=x²+4x+3x+12=x(x+4)+3(x+4)=(x+4)(x+3) x²+8x+15=x²+5x+3x+15=x(x+5)+3(x+5)=(x+5)(x+3) x²+9x+14=x²+7x+2x+14=x(x+7)+2(x+7)=(x+7)(x+2) x+11x+30=x²+6x+5x+30=x(x+6)+5(x+6)=(x+6)(x+5) x²+15x+56=x²+8x+7x+56=x(x+8)+7(x+8)=(x+8)(x+7) x²+12x+35=x²+7x+5x+35=x(x+7)+5(x+7)=(x+7)(x+5) x²-5x+6=x²-2x-3x+6=x(x-2)-3(x-2)=(x-2)(x-3) x²-9x+20=x²-4x-5x+20=x(x-4)-5(x-4)=(x-4)(x-5)

Adaugă răspuns